A preparation method for improving the etching resistance of yttrium oxide coating
By preparing the yttrium oxide coating on the surface of the alumina and forming oxygen vacancy therein, the problem of insufficient etch resistance of the alumina ceramic coating during plasma etching is solved, and higher physical etch resistance and lower maintenance costs are achieved.
Patent Information
- Application Number
- CN202411206382.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-08-30
AI Technical Summary
The existing alumina ceramic coatings have insufficient etch resistance during plasma etching, resulting in high maintenance costs and high replacement frequency of equipment parts.
The physical etch resistance of the yttrium oxide coating is improved by preparing the yttrium oxide coating on the surface of the alumina and forming oxygen vacancy in the yttrium oxide coating through oxygen plasma.
It significantly improves the physical etching resistance of yttrium oxide coating, and reduces the maintenance cost and replacement frequency of equipment parts.
Smart Images

Figure CN119082684B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of material surface treatment technology, and in particular to a method for preparing yttrium oxide coatings with improved etching resistance. Background Technology
[0002] Currently, in the semiconductor industry, dense, high-purity alumina ceramic coatings are commonly used to protect the surfaces of internal components in etching process cavities. However, with the increase in plasma power and density, higher requirements are being placed on the etching resistance of the inner walls of the etching process cavities. Improving the plasma etching resistance of alumina ceramic materials through surface coating is an effective method.
[0003] In existing research, yttrium oxide is a material with excellent resistance to plasma etching and can effectively reduce contaminant particles generated during etching. Physical etching is an important component of plasma etching, and improving resistance to physical etching can lead to even better resistance to plasma etching. Currently, the durability and reliability of equipment are mainly improved by preparing yttrium oxide coatings on alumina surfaces, while further improving the physical etching resistance of yttrium oxide coatings will effectively reduce the maintenance costs and replacement frequency of equipment components. Summary of the Invention
[0004] Based on this, the purpose of the present invention is to provide a method for improving the etching resistance of yttrium oxide coatings by forming oxygen vacancies in the yttrium oxide coatings to improve the physical etching resistance of the yttrium oxide coatings.
[0005] A method for preparing yttrium oxide coatings with improved etching resistance includes the following steps:
[0006] Step S10: After the ultrasonically cleaned high-purity sintered alumina substrate is sent into the coating process chamber, the coating process chamber is evacuated to achieve the preset vacuum level.
[0007] Step S11: Argon gas is introduced into the coating process chamber through the first gas ion source, and after ionization, argon plasma is released to perform plasma cleaning on the high-purity sintered alumina substrate.
[0008] Step S12: A yttrium oxide coating is deposited on the surface of a high-purity sintered alumina substrate after plasma cleaning using magnetron sputtering. At the same time, oxygen is introduced into the coating process chamber through a second gas ion source, and oxygen plasma is released after ionization to form oxygen vacancies in the yttrium oxide coating.
[0009] Compared with the prior art, in this invention, oxygen plasma is used to participate in the deposition process of yttrium oxide coating to form oxygen vacancies in yttrium oxide coating, thereby improving the physical etching resistance of yttrium oxide coating.
[0010] Furthermore, in step S10, the high-purity sintered alumina matrix is sintered by cold isostatic pressing and has a purity of 99.9%.
[0011] Furthermore, in step S10, the preset vacuum level range is 8 × 10⁻⁶. -4 ~1×10 -3 Pa.
[0012] Furthermore, in step S11, the first gas ion source is a linear anodic ion source with a voltage range of 500–800V and a bombardment time of 10–30min.
[0013] Furthermore, in step S12, the power supply used for magnetron sputtering is a pulsed DC power supply with a frequency range of 20 to 40 kHz, a duty cycle of 30 to 80%, and a sputtering voltage range of 400 to 600 V.
[0014] Furthermore, the thickness of the yttrium oxide coating is 1–5 μm.
[0015] Furthermore, in step S12, the second gas ion source is a linear anodic ion source, and the voltage is regulated in a constant voltage mode, with a voltage range of 500 to 1000V, and the working time is the same as the deposition time.
[0016] Furthermore, in step S12, the distance between the sputtering cathode and the surface to be coated is 7-10 cm. Attached Figure Description
[0017] Figure 1 This is a flowchart of the preparation method for improving the etching resistance of yttrium oxide coating in this invention;
[0018] Figure 2(a) is a physical image of the yttrium oxide coating before physical etching, which was deposited without the participation of a gas ion source in this invention;
[0019] Figure 2(b) is a physical image of the yttrium oxide coating after physical etching without the participation of a gas ion source in the deposition of the present invention;
[0020] Figure 2(c) is a physical image of the yttrium oxide coating deposited with the participation of a 500V gas ion source in this invention before physical etching.
[0021] Figure 2(d) is a physical image of the yttrium oxide coating deposited by the 500V gas ion source in this invention after physical etching.
[0022] Figure 2(e) is a physical image of the yttrium oxide coating deposited with the participation of a 1000V gas ion source in this invention before physical etching.
[0023] Figure 2(f) is a physical image of the yttrium oxide coating after physical etching, which was deposited using a 1000V gas ion source in this invention.
[0024] Figure 3 This is a graph showing the variation of oxygen vacancy concentration in the yttrium oxide coating under different oxygen plasma energies as characterized by EPR in this invention.
[0025] Figure 4(a) is a SEM image of the yttrium oxide coating before physical etching in this invention, which was deposited without the participation of a gas ion source.
[0026] Figure 4(b) is a SEM image of the yttrium oxide coating after physical etching without the participation of a gas ion source in the deposition of the present invention.
[0027] Figure 4(c) is a SEM image of the yttrium oxide coating deposited with the participation of a 500V gas ion source in this invention before physical etching.
[0028] Figure 4(d) is a SEM image of the yttrium oxide coating deposited by the 500V gas ion source in this invention after physical etching.
[0029] Figure 4(e) is a SEM image of the yttrium oxide coating deposited by the 1000V gas ion source in this invention before physical etching.
[0030] Figure 4(f) is a SEM image of the yttrium oxide coating after physical etching, which was deposited using a 1000V gas ion source in this invention.
[0031] Figure 5(a) is a SEM cross-sectional view of the yttrium oxide coating before physical etching in the present invention, which was deposited without the participation of a gas ion source.
[0032] Figure 5(b) is a SEM cross-sectional view of the yttrium oxide coating after physical etching without the participation of a gas ion source in the deposition of the present invention;
[0033] Figure 5(c) is a SEM cross-sectional view of the yttrium oxide coating deposited with the participation of a 500V gas ion source in this invention before physical etching.
[0034] Figure 5(d) is a SEM cross-sectional view of the yttrium oxide coating deposited by the 500V gas ion source in this invention after physical etching.
[0035] Figure 5(e) is a SEM cross-sectional view of the yttrium oxide coating deposited by the 1000V gas ion source in this invention before physical etching;
[0036] Figure 5(f) is a SEM cross-sectional view of the yttrium oxide coating deposited by the 1000V gas ion source in this invention after physical etching.
[0037] Figure 6 This is a comparison of the physical etching rates of yttrium oxide coatings with different oxygen vacancy concentrations in this invention.
[0038] Figure 7(a) shows the XRD patterns of the yttrium oxide coating before and after physical etching in the present invention, which was deposited without the participation of a gas ion source.
[0039] Figure 7(b) shows the XRD patterns of the yttrium oxide coating deposited with the participation of a 500V gas ion source in this invention before and after physical etching.
[0040] Figure 7(c) shows the XRD patterns of the yttrium oxide coating deposited using a 1000V gas ion source in this invention before and after physical etching.
[0041] The following detailed description, in conjunction with the accompanying drawings, will further illustrate the present invention. Detailed Implementation
[0042] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Several embodiments of the invention are illustrated in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete.
[0043] Please see Figure 1 An embodiment of the present invention provides a method for preparing a yttrium oxide coating with improved etching resistance, comprising the following steps:
[0044] Step S10: After the ultrasonically cleaned high-purity sintered alumina substrate is sent into the coating process chamber, the coating process chamber is evacuated to achieve the preset vacuum level.
[0045] Specifically, in step S10, the high-purity sintered alumina matrix is sintered by cold isostatic pressing and has a purity of 99.9%.
[0046] Specifically, the cleaning medium for ultrasonic cleaning is anhydrous ethanol. After cleaning, the substrate is dried in an inert nitrogen gas. After drying, the high-purity sintered alumina substrate is sent into a vacuum chamber.
[0047] Specifically, the preset vacuum level range is 8×10. -4 ~1×10 -3 Pa.
[0048] Step S11: Argon gas is introduced into the coating process chamber through the first gas ion source, and after ionization, argon plasma is released to perform plasma cleaning on the high-purity sintered alumina substrate.
[0049] It should be noted that the purpose of cleaning in this step is to remove impurities (mainly water molecules and organic matter) from the substrate surface and to increase the activation energy to enhance the adhesion between the membrane and the substrate.
[0050] Specifically, in step S11, the first gas ion source is a linear anodic ion source with a voltage range of 500–800V and a bombardment time of 10–30 min.
[0051] In step S12, a yttrium oxide coating is deposited on the surface of a high-purity sintered alumina substrate after plasma cleaning using magnetron sputtering. At the same time, oxygen is introduced into the coating process chamber through a second gas ion source, and oxygen plasma is released after ionization to form oxygen vacancies in the yttrium oxide coating.
[0052] It should be noted that physical etching is a part of plasma etching in semiconductor manufacturing processes. Its main principle is the removal and destruction of material caused by the high-energy bombardment of the material surface by argon plasma in a vacuum environment. Resistance to physical etching is manifested in its resistance to argon plasma bombardment damage and is reflected in the etching rate; a higher etching rate results in poorer resistance, and vice versa.
[0053] Specifically, the oxygen vacancies in this application are point defects existing at the atomic level of yttrium oxide, namely, vacancies formed by the absence of oxygen atoms, which can improve the physical etching resistance of the yttrium oxide coating. This application improves the physical etching resistance of the yttrium oxide coating by using oxygen plasma in the deposition process of the yttrium oxide coating to form oxygen vacancies in the coating. Furthermore, the energy of the oxygen plasma can be controlled by adjusting the voltage in a constant voltage mode, thereby achieving control over the oxygen vacancy concentration.
[0054] It should be noted that the introduction of oxygen vacancies in this application mainly stems from the bombardment effect of oxygen ions during the deposition of the yttrium oxide coating. The introduction of oxygen vacancies alters the bonding between oxygen and yttrium atoms in the yttrium oxide lattice: 1. Due to the absence of oxygen atoms, the originally bonded yttrium atoms and their surrounding oxygen atoms shift to varying degrees; 2. This atomic shift leads to lattice distortion, while simultaneously reducing the distance between yttrium and oxygen atoms and shortening the bond length; 3. The shortened bond length increases the energy of the yttrium-oxygen bond, thus increasing the energy required to break the bond. The changes in the bonding between yttrium and oxygen atoms caused by oxygen vacancies mean that the high-energy bombardment by argon ions during physical etching requires greater energy and a longer time to break the bonds, thereby improving the physical etching resistance of the yttrium oxide coating. Increasing the oxygen vacancy concentration can effectively improve the etching resistance of the yttrium oxide coating without changing its cubic crystal phase, as detailed in the embodiments.
[0055] Specifically, in step S12, the power supply used for magnetron sputtering is a pulsed DC power supply with a frequency range of 20 to 40 kHz, a duty cycle of 30 to 80%, a sputtering voltage range of 400 to 600 V, and a yttrium oxide coating thickness of 1 to 5 μm.
[0056] Furthermore, the distance between the sputtering cathode and the surface to be coated is 7–10 cm.
[0057] Specifically, in step S12, the second gas ion source is a linear anodic ion source, and the voltage is regulated in a constant voltage mode, with a voltage range of 500 to 1000V, and the working time is the same as the deposition time.
[0058] Example
[0059] The preparation method of this application will be described in detail below with reference to specific embodiments:
[0060] Please see Figures 2(a)-2(f) A high-purity sintered alumina substrate with dimensions of 30×30×3mm was ultrasonically cleaned in anhydrous ethanol, then dried with nitrogen. After treatment, it was placed in a vacuum chamber and evacuated. The vacuum level reached 1×10⁻⁶. -3 Ion bombardment cleaning was initiated at Pa. Reactive sputtering was performed using a pulsed DC power supply at a 50% duty cycle, a frequency of 20 kHz, and a power of 400 W. Oxygen was introduced through a gas ion source, and sputtering was conducted at 1000 V, 500 V, and no voltage. After 2 hours of sputtering, the yttrium oxide coating thickness on the surface of the high-purity sintered alumina was approximately 3 μm. After deposition, the three yttrium oxide coating samples were simultaneously subjected to physical etching under the same conditions, and the samples before and after etching were characterized by electron paramagnetic resonance (EPR), scanning electron microscopy (SEM), and X-ray diffraction (XRD).
[0061] Please see Figure 3 The oxygen vacancy concentrations of three different yttrium oxide coatings were characterized using electron paramagnetic resonance (EPR), revealing a clear trend. EPR is a technique for detecting unpaired electrons in paramagnetic materials, allowing for precise atomic-level data acquisition. These materials absorb radiation of specific frequencies when exposed to electromagnetic radiation in a specific magnetic field. EPR is highly sensitive to identifying oxygen vacancies in metal oxide materials, providing direct information about defect locations. The g-tensor is an important data point reflecting defect characteristics; in materials containing oxygen vacancies, the g-tensor is approximately 2.00. The EPR results indicate that different concentrations of oxygen vacancies were formed during coating deposition. It can be seen that the EPR curves of the three samples largely overlap, showing a dominant signal P1 with a dominant g-tensor of 2.009, while the lower-intensity signal P2 has a dominant g-tensor of 2.007. The oxygen vacancy concentration gradually increases with increasing oxygen plasma energy.
[0062] Please see Figures 4(a) to 6SEM was used to visually characterize the surface changes and cross-sectional thicknesses of three different yttrium oxide coatings before and after physical etching, and the corresponding etching rates were calculated to reflect their resistance to physical etching. SEM results showed that the microstructures of the yttrium oxide coatings deposited by the three different gas ion source voltages were almost identical. Before physical etching, the yttrium oxide coating surface exhibited a dense and uniform structure without obvious defects; after etching, the surface showed obvious signs of damage and increased roughness. Before physical etching, the thickness of the three different yttrium oxide coatings gradually decreased with increasing gas ion source voltage, and after etching, varying degrees of thinning occurred, which is attributed to the improved resistance to physical etching. After precise measurement of the cross-sectional thicknesses of three different yttrium oxide coatings before and after physical etching, the results showed that the thicknesses of the yttrium oxide coatings before etching, with no voltage, 500V, and 1000V gas ion sources were 3220, 3170, and 2620, respectively. After 4 hours of etching, the thicknesses decreased to 2740, 2910, and 2460, with reductions of 480, 260, and 160, respectively. The etching rates were 2.00, 1.08, and 0.67 nm / min, respectively. The etching rate of the 500V sample decreased by approximately 84.6% compared to the no-voltage sample, and the etching rate of the 1000V sample decreased by approximately 200% and 62.5% compared to the no-voltage and 500V samples, respectively.
[0063] Please see Figures 7(a) to 7(c) XRD was used to characterize the crystal structures of three different yttrium oxide coatings before and after physical etching. The results showed that the yttrium oxide coatings deposited using the three different gas ion source voltages had the same crystal phase, namely a c-type cubic crystal structure, indicating that changes in oxygen vacancy concentration had no significant effect on the crystal structure. However, with increasing voltage, the peak intensity of this crystal phase gradually decreased, indicating that the oxygen vacancy concentration cannot be increased indefinitely. Furthermore, with increasing voltage, the grain size of the three different yttrium oxide coatings gradually increased. After physical etching, the crystal phase of the three different yttrium oxide coatings remained unchanged, while the grain size decreased slightly.
[0064] In summary, this invention increases the oxygen vacancy concentration of the yttrium oxide coating by using oxygen plasmas of different energies released at different voltages to participate in the deposition of the yttrium oxide coating without changing the crystal structure. This significantly reduces the physical etching rate and improves the physical etching resistance of the yttrium oxide coating, providing a new production solution for industrial production of yttrium oxide coatings with superior plasma etching resistance.
[0065] In this specification, the various embodiments are described in a progressive manner, with each embodiment focusing on its differences from other embodiments. Similar or identical parts between embodiments can be referred to interchangeably. Furthermore, the above-described embodiments merely illustrate several implementation methods of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this patent should be determined by the appended claims.
Claims
1. A preparation method for improving the etching resistance of yttrium oxide coating, characterized in that: The following steps are involved: Step S10, after the high-purity sintered alumina substrate after ultrasonic cleaning is sent into the coating process chamber, the coating process chamber is evacuated to reach a preset vacuum degree; Step S11, introducing argon gas into the coating process chamber through a first gas ion source, releasing argon plasma after ionization, so as to perform plasma cleaning on the high-purity sintered alumina substrate, wherein the first gas ion source is a linear anode ion source, the voltage range is 500 to 800 V, and the bombardment time is 10 to 30 min; Step S12, using magnetron sputtering to deposit an yttrium oxide coating on the surface of the high-purity sintered alumina substrate after plasma cleaning, and at the same time, introducing oxygen into the coating process chamber through the second gas ion source, releasing oxygen plasma after ionization, so as to form oxygen vacancies in the yttrium oxide coating, wherein the power supply used for magnetron sputtering is a pulsed DC power supply with a frequency range of 20 to 40 kHz, a duty cycle of 30 to 80%, and a sputtering voltage range of 400 to 600 V. The second gas ion source is a linear anode ion source, and the voltage is regulated in a constant voltage mode with a voltage range of 500 to 1000 V. The working time is the same as the deposition time.
2. The method for preparing a yttrium oxide coating for improving its etching resistance according to claim 1, characterized in that: In step S10, the high-purity sintered alumina substrate is sintered by cold isostatic pressing, and the purity is 99.9%.
3. The method for preparing a yttrium oxide coating for improving its etching resistance according to claim 1, characterized in that: In step S10, the range of the vacuum degree is preset to 8×10 -4 ~ 1×10 -3 Pa.
4. The method for preparing a yttrium oxide coating for improving its etching resistance according to claim 1, characterized in that: The thickness of the yttrium oxide coating is 1 ~ 5μm.
5. The method for improving the etching resistance of yttrium oxide coating according to any one of claims 1 to 4, characterized in that: In step S12, the distance between the sputtering cathode and the surface to be coated is 7 to 10 cm.
Citation Information
Patent Citations
Preparation method of performance-improved Y2O3 erosion-resistant ceramic coating
CN103074562A
Preparation method of low-roughness yttrium oxide coating
CN117265480A
Cited By
Plasma spraying process of high-corrosion-resistance yttrium oxide coating and gradient structure design method
CN121472758A